Encapsulation of tamoxifen citrate conjugated with magnetite nanoparticle - Albert, Emmellie Laura (2017)
Cancer chemotherapy drugs are not specific on their metabolic pathways to the cancer cell. Therefore, there is a need to overcome this disadvantages by applying targeted drug delivery using composite nanoparticles. Similarly, tamoxifen citrate (TAM) also suffer from this disadvantages. TAM is a drug used for breast cancer treatment. So, current investigations are proposing the usage of magnetite nanoparticles (MNP) as an anti-cancer drug carrier because of its biocompatibility, ultrafine size, and its superparamagnetic nature. In this study, poly (d,l-lactice-co-glycolide acid) (PLGA) were used to encapsulated both MNP and TAM to form a multifunctional nanoparticle which have both the superparamagnetic properties of MNP and therapeutic ability of TAM. MNP were synthesized via the co-precipitation method. Then, it was coated with oleic acid (OA) to reduce the aggregation and it was abbreviated as OAMNP. Formation of functionalized OAMNPs with TAM using PLGA (TAM-PLGA-OAMNP) was obtained by oil in water emulsion evaporation technique. The XRD pattern showed that crystalline phase of the MNP is inverse spinel cubic of Fe3O4. After modification, FTIR spectra revealed that the TAM were successfully encapsulated into the PLGA matrixes. By using TEM, the particles size is determine by 131 ± 28 nm for TAM-PLGA-OAMNP. The VSM analysis for TAM-PLGA-OAMNP showed no hysteresis loop indicating superparamagnetic characteristic. This projects also presents a discussion on the optimum condition for colloid stability for TAM-PLGA-OAMNPs based on the aggregation and sedimentation. Finally, TAM released behavior is studied. TAM-PLGA-OAMNPs followed a biphasic phase released.